Mind Management and Motivation for HRD: A Bhagavad Gita perspective (International Journal of Environmental Sciences, 2025)
In today’s rapidly evolving organizational environment, effective mind management and the cultivation of intrinsic motivation have become essential pillars of Human Resource Development (HRD). Conventional HRD strategies often emphasize external rewards, skills training, and structural engagement, frequently neglecting the inner psychological and ethical foundations essential for sustained growth and well-being. This paper explores how insights from the Bhagavad Gita can transform mind management and motivation within HRD.This paper employs a qualitative hermeneutic and interpretive approach. By analyzing key verses, it brings forth concepts such as Karma Yog (performing duties without attachment to outcomes), the guiding role of intellect (Buddhi) in regulating desires and emotions, and practical disciplines like Abhyasa (consistent practice) and Vairagya (detachment). The study emphasizes that by managing desires and fostering equanimity, individuals can reduce stress and fatigue. This also helps strengthen resilience, support ethical choices, and promote more meaningful participation at work. By integrating these significant teachings with modern HRD needs, the paper proposes strategies for fostering intrinsic motivation, emotional regulation, and a balanced pursuit of organizational goals. Thus, the paper positions the Bhagavad Gita as a valuable resource for creating holistic HRD models that nurture both individual growth and organizational success.